Factors involving in healthcare professionals’ decision-making process regarding the use of restrictive care practices in adult mental health inpatient units: A protocol for an umbrella review - Zelalem Belayneh; Biazin Yenealem; Alemayehu Molla; Nigus Alemnew; Temesgien Ergetie; Workua Mekonnen; Birhanie Mekuriaw (PLoS ONE, 2025)
Introduction The use of restrictive care practices, such as physical restraint, seclusion, and chemical restraint, remains common practices, yet controversial aspect of mental health care, particularly in inpatient settings. Variations in legal definitions and protocols guiding the implementation of these practices often create legal and ethical dilemmas for professionals when deciding whether to implement such practices in certain circumstances. This leads them to rely on subjective decision-making, which is further shaped by epistemic disparities stemming from differences in knowledge, perspectives, and experiences that impact professionals’ understanding and implementation of restrictive practices. Aims This is a study protocol for an upcoming umbrella review aiming to identify and analyse the thematic elements that affect healthcare professionals’ decision-making regarding the uimplementations of restrictive care practices in adult mental health inpatient settings. Methods This protocol outlines the approach for an umbrella review. The review will conduct a systematic literature search of electronic databases (Scopus, CINAHL, Embase, OVID, PsycINFO, Cochrane Reviews, and Web of Science) using comprehensive search strings, as well as a manual review of reference lists from included reviews. Only review studies will be considered. Textual data discussing issues related to professionals’ decision-making regarding the use of restrictive care practices will be extracted from each study, coded, and analysed using inductive content analysis. This protocol has been reported according to the PRISMA-P Checklist. Discussion The findings from this review will provide valuable insights into the key factors influencing the implementation of restrictive practices in adult mental health inpatient settings. The factors identified in this umbrella review will be applied in clinical practices to guide healthcare practitioners in considering and navigating various contexts when deciding how and in which situations restrictive care practices should be implemented. This contributes to the current global effort in promoting more patient-centered, transparent, evidence-based and accountable practices, while minimizing restrictive interventions. It will also inform future training, practice, and policy interventions aiming at reducing the use of restrictive measures in adult mental health settings. Protocol registration: This protocol has been registered in PROSPERO (CRD-42024581848).